Calcium Pyrophosphate Dihydrate Deposition Disease in Young Patients: Two Case Reports - Geetha WICKREMATILAKE (Archives of Rheumatology, 2017)
Calcium pyrophosphate deposition disease (CPDD) is a type of arthritis caused by the deposition of calcium pyrophosphate crystals, and may present as either acute or chronic arthritis. Development of CPPD crystal deposition disease in young people may be associated with metabolic diseases such as hemochromatosis, hyperparathyroidism, hypomagnesemia, Wilson’s disease, hypothyroidism, gout, acromegaly, and X-linked hypophosphatemic rickets. Therefore, investigations for a predisposing metabolic condition are advised in young-onset polyarticular CPPD crystal deposition disease. In this article, we report two young patients who were investigated for recurrent joint pain due to CPPD disease.